Reliability and validity of the East Asian children's version of mini-MACS in children with cerebral palsy - Xiaohui Hou; Xiaohui Hou; Huiying Qiu; Liru Liu; Yinhua Li; Lu He; Jinling Li; Hongmei Tang; Kaishou Xu (Frontiers Media S.A., 2022)
BackgroundMini-Manual Ability Classification System (Mini-MACS) was developed for children with cerebral palsy aged 1-4 years, but its validity and reliability in different cultures are unavailable yet. This study was to determine the reliability and validity of Mini-MACS in East Asian children with cerebral palsy and investigate the correlation between Mini-MACS and Gross Motor Function Classification System.MethodsOne hundred and four East Asian children with cerebral palsy aged 12-48 months were classiﬁed by one of their parents, an occupational therapist, and a physical therapist with Mini-MACS. The results were analyzed for inter-rater reliability by using intraclass correlation coefficient (ICC). The Nine-hole Peg Test was used for the criterion-related validity analysis, and parents retested their children after 2 weeks to evaluate test-retest reliability. Gross Motor Function Classification System levels were also collected to investigate the correlation with Mini-MACS.ResultsGood inter-rater reliability among the occupational therapist, physical therapist, and parents was found [ICC = 0.984 (95% confidence interval, CI, 0.976-0.989), 0.973 (95% CI 0.960-0.982), and 0.966 (95% CI 0.950-0.977), respectively; p < 0.01]. The test-retest reliability in parents was almost perfect [ICC = 0.985 (95% CI 0.977-0.990), p < 0.01]. Mini-MACS had consistency with the Nine-hole Peg Test (r = 0.582, 0.581, and 0.566, respectively; p < 0.01). A correlation was found between Gross Motor Function Classification System and Mini-MACS (r = 0.626, 0.596, and 0.598, respectively; p < 0.01).ConclusionThe Mini-MACS demonstrates evidence that it is a valid and reliable tool to classify manual ability in East Asian children with cerebral palsy and is also positively related to the Gross Motor Function Classification System.